(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The purpose of this paper is to consider inclusive practices that allow for more entrepreneurship opportunities in the healthcare industry. The current environment for healthcare organizations, including their governing structure and culture, may be barriers to inclusive entrepreneurship. Supporting inclusive entrepreneurship can help to promote entrepreneurial activities, ultimately driving innovation and health advancements. This topic is important for healthcare workers, administrators, and policymakers alike. By working towards inclusive entrepreneurship, healthcare organizations have the opportunity to improve care quality outcomes for the patients they serve.